Bioaccumulation of Trace Metals in Two Species of Crabs from Chilika Lagoon, East Coast of India - Lakshman, Nayak; Priyadarsini, Pati Mitali; Das, Sharma Satyabrata (Journal of Atmosphere, 2015)
The present study was conducted to determine heavy metal concentration (Mn, Fe, Cu and Zn) in body organ of two important species of crab (Scylla serrata and Portunus pelagicus) from Chilika lagoon. The heavy metal concentration observed in the muscles, body carapace and leg carapace. The highest length was 13.2 cm and weight was 238.52 gm observed in Scylla serrata. The highest length and weight of Portunus pelagicus was 8.5 cm and 92.3 gm. The metal concentration of Mn, Fe, Cu and Zn in the leg carapace varied from 4.2 to 5.5 ppm, 16.6 to 18.4 ppm, 5.7 to 9.5 ppm and 152 to 211 ppm dry weight respectively. Similarly the concentration of metals in the muscle were in the range of 3.8 to 5.1 ppm, 14.4 to 17.5 ppm, 4.8 to 7.4 ppm and 129 to 188 ppm dry weight for Mn, Fe, Cu and Zn respectively. Metal concentrations in the body carapace of the above metals varied from 3.8 to 5.3 ppm, 15.2 to 18.2 ppm, 5.8 to 8.6 ppm and 152 to 193 ppm dry weight respectively. The concentration of metals was lowest in the muscle as compared to other organs. Scylla serrata contained higher concentration of metals in the muscle as compared to Portunus pelagicus. There was no correlation between body size and heavy metal concentration. The metal concentration found in the present study was lower to metal concentration levels of crab collected from other parts of the world. Therefore, there is no public health problem if the crabs will consume it.